Holocene reef growth over irregular Pleistocene karst confirms major influence of hydrodynamic factors on Holocene reef development. (15th January 2018) - Salas-Saavedra, Marcos; Dechnik, Belinda; Webb, Gregory E.; Webster, Jody M.; Zhao, Jian-xin; Nothdurft, Luke D.; Clark, Tara R.; Graham, Trevor; Duce, Stephanie
Abstract: Many factors govern reef growth through time, but their relative contributions are commonly poorly known. A prime example is the degree to which modern reef morphology is controlled by contemporary hydrodynamic settings or antecedent topography. Fortunately, reefs record essential information for interpreting palaeoclimate and palaeoenvironment within their structure as they accrete in response to environmental change. Five new cores recovered from the margin of Heron Reef, southern Great Barrier Reef (GBR), provide new insights into Holocene reef development and relationships between Holocene reefs and Pleistocene antecedent topography, suggesting much more irregular underlying topography than expected based on the configuration of the overlying modern reef margin. Cores were recovered to depths of 30 m and 94 new 230 Th ages document growth between 8408 ± 24 and 2222 ± 16 yrs. BP. One core penetrated Pleistocene basement at ∼15.3 m with Holocene reef growth initiated by ∼8.4 ka BP. However, 1.83 km west along the same smooth margin, four cores failed to penetrate Pleistocene basement at depths between 20 and 30 m, suggesting that the margin at this location overlies a karst valley, or alternatively, the antecedent platform does not extend there. A 48 m-long margin-perpendicular transect of three cores documents the filling of this topographic low, at least 30 m beneath the current reef top, with seaward lateral accretion at a rate of 34.3 m/ka. Cores indicate steady vertical and lateral accretion between 3.2 and 1.8 ka BP with no evidence of the hiatus in reef flat progradation seen in most other offshore reefs of the GBR at that time. These cores suggest that the relative protection afforded by the valley allowed for unconsolidated sediment to accumulate, enabling continuous progradation even when other areas of the reef flat appear to have 'turned off'. Additionally, the cores suggest that although reefs in the southern GBR clearly owe their location to Pleistocene antecedent topography, modern reef morphology at sea level primarily reflects the interaction of Holocene reef communities with contemporary hydrodynamics. Highlights: Holocene reef development is highly influenced by hydrodynamic factors. Holocene reef growth obscured significant Pleistocene antecedent topography. Sea level change triggered different responses in different areas of the same reef.